Can't you see I love you? Recognizing Displays of Love and the Implications for Marital Satisfaction - Jelić, Margareta; Mihić, Ivana; Mihić, Vladimir (2012)
Although an individual may report showing love to his or her spouse in a particular way, there is no guarantee the partner will notice the behavior, much less recognize it as a display of love. In the current study, we investigated whether husbands and wives see their partner expressing love in the ways partners indicate they show it, and if feelings of marital satisfaction are higher among spouses whose reported displays of love are better recognized as such by their partners. To accomplish this objective, we asked 302 married couples from Croatia and 456 married couples from Serbia to indicate the ways they show love to their partner, the ways their partner shows love to them. All analyses controlled for spouses’ feelings of marital love. Overall, results showed concordance between spousal pairs in perceptions of each other’s propensity to show their love in particular ways. Partners showed the most agreement for displays of love through physical and verbal affection. Interestingly, husbands were better than wives at recognizing their spouses’ reported displays of love. For both husbands and wives, reporting that one’s partner expressed love was tied to higher levels of marital satisfaction.
Projekt MZOS
ENG